Impact of CuO on TeO2–GeO2–ZnO–Al2O3–MgO glass system for ionizing shielding applications - Sayyed, M.I.; Kaky, Kawa M.; Mhareb, M.H.A.; Al-keisy, Amar; Baki, S.O. (Springer, 2023)
In the present study, a set of four glass samples with the composition of (50 − x)TeO2 − 10GeO2 − 20ZnO − 10Al2O3 − 10MgO − xCuO where x = 0.5, 1, 2, and 3 mol% has been investigated. This study explored the physical, mechanical, structural, and radiation shielding capabilities of glass samples. Also, the mechanical parameters of the synthesized glass samples, like elastic modulus, were computed theoretically. The structural behavior of current samples was investigated using Raman spectroscopy to identify functional groups and vibration modes for TeO2 and GeO2. While Fourier transform infrared was utilized to validate the Raman spectroscopy data. The addition of CuO instead of TeO2 enhanced the mechanical parameters. In addition, Phy-X software was used to evaluate the radiation shielding features. The transmission factor (TF) results revealed that to decrease the number of photons that pass through the prepared glass system with increased thickness. Also, the glass with the highest CuO content, Cu4, has the lowest TF, while the sample with the lowest amount of CuO and Cu1 has the greatest TF. According to the results, adding CuO instead of TeO2 enhanced the glass samples’ mechanical and radiation shielding properties, leading to their ability to be used in the radiation shielding field.